Factors Related to the Incidence of Diarrhea in Children Aged 1-3 Years in the Working Area of the Gunung Labu Puskesmas, Kerinci District - Hayu, Ramah; Jesica, Fanny (International Journal of Multidisciplinary Approach Research and Science, 2023)
Diarrhea is Reason death biggest third on toddlers in the world after pneumoniae and disease default . Death rate caused toddlers _ Because diarrhea reached 1.5 million per year . Incident the biggest happened at 2 years First life and decline along with growth children ( Ministry of Health RI, 2017) . Many factors are related with incident diarrhea in toddlers 1-3- years . Research This aim For know related factors _ with incident diarrhea in toddlers aged 1-3- years in the health center Mount Labu, Kayu Aro Barat District , 2022. Type study is study qualitative with approach cross sectional . Data collection has done on the month February 2023 - March 2023 . Population in research This as much 262 people and samples numbered 70 people, engineering taking sample with formula Lemeshow . Data analyzed in a manner univariate with distribution frequency on each one variables and analysis bivariate with using the chi-square test . Statistical test results showing there is connection level knowledge ( p value=0.000), nutritional status ( p value=0.000 ), age wedding early ( p value = 0.000) then can taken conclusion that there is connection level knowledge, status nutrition , age wedding early with incident diarrhea in toddlers aged 1-3 years in the health center Mount Labu, Kayu Aro Barat District , 2022. Recommended to officer health For give counseling health and facilitation Mother in get iformation about disease diarrhea.